2018
DOI: 10.1101/276717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why should mitochondria define species?

Abstract: More than a decade of DNA barcoding encompassing about five million specimens covering 100,000 animal species supports the generalization that mitochondrial DNA clusters largely overlap with species as defined by domain experts. Most barcode clustering reflects synonymous substitutions. What evolutionary mechanisms account for synonymous clusters being largely coincident with species? The answer depends on whether variants are phenotypically neutral. To the degree that variants are selectable, purifying select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 160 publications
0
5
0
Order By: Relevance
“…DNA barcoding relies on the premise that intraspecific sequence differences in a standardized gene fragment are generally smaller than interspecific ones (Meier, Zhang, & Ali, ; Stoeckle & Thaler, ; Wiemers & Fiedler, ). This allows clustering of barcode data into distinct genetic groups, which in most cases reflect actual species boundaries (Stoeckle & Thaler, ).…”
Section: Methodsmentioning
confidence: 99%
“…DNA barcoding relies on the premise that intraspecific sequence differences in a standardized gene fragment are generally smaller than interspecific ones (Meier, Zhang, & Ali, ; Stoeckle & Thaler, ; Wiemers & Fiedler, ). This allows clustering of barcode data into distinct genetic groups, which in most cases reflect actual species boundaries (Stoeckle & Thaler, ).…”
Section: Methodsmentioning
confidence: 99%
“…As such transcripts overlap the coding regions of protein-coding genes, it is difficult to distinguish the potential functional impact of mutations in such elements. Despite all of the above, although it is possible to assess the potential impact of mutations that alter codons but not the amino acid code (the so-called silent mutations) by assessing codon bias index (Levin et al, 2013), only minor phenotypic effects have been demonstrated regarding such in the mitochondria, leading some researchers to argue for lack of selective signatures in most mtDNA mutations (Stoeckle and Thaler, 2018). Nevertheless, phenotypic impact of a mutation is not only limited to the subsequent gene function-an apparently silent mutation could alter a previously un-noticed regulatory element (Blumberg et al, 2018).…”
Section: Identifying the Signatures Of Selection-assessing The Functimentioning
confidence: 99%
“…While it is difficult to isolate nuclear DNA of sufficient quality and quantity from moulted feathers, there are hundreds to thousands of copies of the mtDNA molecule, making it more readily available for analysis. Mitochondrial loci have been shown to be an efficient estimator of recent population divergence (Moore 1995, Zink and Barrowclough 2008, Hung et al 2016, DeSalle et al 2017, Stoeckle and Thaler 2018). While phylogenetic trees reconstructed from phenotypes and mitochondrial or nuclear loci can contradict each other (Griffiths et al 2004, Bensch et al 2006, Yeung et al 2011, Drovetski et al 2018, Harris et al 2018), our data on the geographic distribution of black kite haplogroups correlated well with subspecies ranges inferred from phenotype and migration pathways; hence, we consider that the phylogenetic tree based on the CytB gene fragment adequately reflects actual black kite phylogeny.…”
Section: Discussionmentioning
confidence: 99%